FUN ENGLISH DAN BIMBINGAN BELAJAR BAGI ANAK - ANAK SOS CHILDREN’S VILLAGE BALI - I Gusti Ngurah Bagus Yoga Widiadnya; Purnami, Ida Ayu Oka (Jurnal Abdi Insani, 2024)
In learning a language there are four basic language skills, namely listening, speaking, reading and writing. However, there are three areas that play an important role in supporting these four language skills (Megawati, 2016). The three parts are: pronunciation, vocabulary (words) and punctuation pronunciation. Therefore, many students face obstacles in learning English. These difficulties are also experienced by children at SOS Children's Village Bali, so that in the end they have an impact on their interest in learning English. Seeing these situations and conditions, this is a reason to carry out Community Service because they really need it. The English learning activity in this service is called Fun English and aims to create a fun learning environment. The focus of this fun English activity is to improve reading and speaking skills. This PKM is carried out for children at SOS Children's Village Bali. The method used in this social service is the recitation method. The recitation method is a model of presenting teaching materials by giving assignments to students. The participants who took part were students in primary school and junior high school education backgrounds. The achievement of this PKM is an increase in participants' ability to say vocabulary correctly. Participants have understood how to pronounce punctuation marks correctly. The result of this activity is that participants' concentration and motivation increase, this is proven by the results of the activity evaluation in the post-test. In this way, participants also feel happy and do not feel awkward when participating in all the fun English activities at PKM.